Implementation of the Student Teams Achievement Divisions (STAD) Model Using Kahoot Application in Sociology Learning to Increase Students' Learning Activity - Rajab, Siti Chintya Wulan; Syamsuri, Syamsuri; Wijaya, Tri; Prancisca, Stella (Universitas Tanjungpura, 2025)
The main purpose of this study was to determine whether the implementation of the Student Teams Achievement Divisions (STAD) model using the Kahoot application in sociology learning can increase the learning activeness of class X H students at SMA Negeri 1 Pontianak. This research uses Classroom Action Research (PTK) which consists of 2 cycles. Each PTK cycle is carried out through systematic stages such as planning, implementation, observation, and reflection. Data collection techniques applied in this study were in-depth observation techniques using student learning activeness observation sheets and documentation. Indicators of learning activeness observed include: (1) listening to the material explained by the teacher, (2) the ability to ask questions, (3) answer questions, (4) participation in group discussions, (5) making notes summarizing the subject matter, (6) the ability to express opinions, and (7) the ability to present the results of group discussions (presentations) or provide responses to groups that make presentations. The number of students involved in this study was 36 people. The results prove that there is an increase in student learning activeness from cycle 1 to cycle 2 with an average of 73.71% in cycle I and 87.30% in cycle II. The application of the STAD model by utilizing the Kahoot application has proven effective in increasing the activeness of students in learning Sociology in class. Through learning with heterogeneous group members, learners are encouraged to help each other understand the material and discuss actively. Then, Kahoot's interactive features, such as giving points and rankings, triggered learners' enthusiasm in answering quizzes and competing healthily to get the best score. This fun and interesting learning atmosphere is able to increase learners' active participation during the Sociology learning process.